Phytochemical evaluation and in vitro antioxidant studies of selected species of Gomphostemma Wall. ex Benth. from Western Ghats - Sajitha, M. K; Thoppil, J. E. (Journal of Drug Delivery and Therapeutics, 2018)
Plants are a rich source of bioactive compounds and have played a vital role in traditional medicine. Plant derived compounds are proved to have less side effects as compared to synthetic compounds. However, a truncated history on the contribution of plants to medicine together with lack of validation of plant derived components have led to massive research in phytochemistry and allied fields. Present study was intended to identify as well as to assess and compare different phytochemicals and antioxidant potential of selected taxa of Gomphostemma endemic to Western Ghats. Methanolic extracts of aerial parts of Gomphostemma heyneanum var. heyneanum, Gomphostemma heyneanum var. rottleri and Gomphostemma eriocarpum were subjected to preliminary phytochemical screening. Quantitative estimation of phenols and flavonoids was done with Folin-Ciocalteu method and modified Aluminium chloride method respectively. Antioxidant potential was examined by DPPH assay, Hydroxyl radical scavenging assay and Reducing power activity. Preliminary screening indicated the presence of many secondary metabolites like phenols, flavonoids, alkaloids, terpenoids and steroids. Results of quantitative estimation revealed that G. heyneanum var. heyneanum has the highest concentration of phenols and flavonoids. Antioxidant potential determined in terms of inhibition percentage also displayed that Gomphostemma species have significant radical scavenging activity. The antioxidant potential exhibited by the plant species may be attributed to their phenol and flavonoid content.Keywords: Phytochemical constituents, Gomphostemma, Quantitative estimation, Total phenolics, Flavonoids, Antioxidant activity, DPPH assay, Hydroxyl radical scavenging assay, Reducing power activity.